Development of the ‘Canteen Scan’: an online tool to monitor implementation of healthy canteen guidelines - Evenhuis, I. J. (BMC Public Health, 2018)
BACKGROUND: To improve the availability and accessibility of healthier food and drinks in schools, sports and worksites canteens, national Guidelines for Healthier Canteens were developed by the Netherlands Nutrition Centre. Until now, no tool was available to monitor implementation of these guidelines. This study developed and assessed the content validity and usability of an online tool (the ‘Canteen Scan’) that provides insight into and directions for improvement of healthier food products in canteens. METHODS: The Canteen Scan was developed using a three-step iterative process. First, preliminary measures and items to evaluate adherence to the guidelines were developed based on literature, and on discussions and pre-tests with end-users and experts from science, policy and practice. Second, content validity of a paper version of the Canteen Scan was assessed among five end-users. Third, the online Canteen Scan was pilot tested among end-users representing school canteens. Usability was measured by comprehensibility, user-friendliness, feasibility, time investment, and satisfaction. RESULTS: The content validity of the Canteen Scan was ensured by reaching agreement between stakeholders representing science, policy and practice. The scan consists of five elements: 1) basic conditions (e.g. encouragement to drink water and availability of policy regarding the guidelines), 2) product availability offered on displays (counter, shelf) and 3) in vending machines, 4) product accessibility (e.g. promotion and placement of products), and 5) an overall score based on the former elements and tailored feedback for creating a healthier canteen. The scan automatically classifies products into healthier or less healthy products. Pilot tests indicated good usability of the tool, with mean scores of 4.0–4.6 (5-point Likert scale) on the concepts comprehensibility, user-friendliness and feasibility. CONCLUSION: The Canteen Scan provides insight into the extent to which canteens meet the Dutch Guidelines for Healthier Canteens. It also provides tailored feedback to support adjustments towards a healthier canteen and with the scan changes over time can be monitored. Pilot tests show this tool to be usable in practice.